2019
DOI: 10.1371/journal.pone.0211640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe polyhandicap on parents’ quality of life: A large French cross-sectional study

Abstract: BackgroundPolyhandicap (PLH) is a condition of severe and complex disabilities and is defined by a combination of profound intellectual impairment and serious motor deficits. Parents of PLH individuals are chronically confronted with stressful situations. The aims of this study are i) to assess and compare the quality of life (QoL) of a large panel of parents of PLH individuals with age- and gender-matched controls and ii) to identify potential determinants of parents’ QoL.MethodWe conducted a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…However, as the PLH individual aged, the burden level rose, which could be explained by the probable older age of caregivers. An interesting genre difference emerged in the lack of familial support for caregiving: parents of male individuals had less individual support than parents of female individuals confirming our previous results, which demonstrated a lower QoL for the parents of a male child than parents of a female child 27. This finding referred to the social representations that individuals develop.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, as the PLH individual aged, the burden level rose, which could be explained by the probable older age of caregivers. An interesting genre difference emerged in the lack of familial support for caregiving: parents of male individuals had less individual support than parents of female individuals confirming our previous results, which demonstrated a lower QoL for the parents of a male child than parents of a female child 27. This finding referred to the social representations that individuals develop.…”
Section: Discussionsupporting
confidence: 85%
“…As expected,11 27 28 the caregivers’ health status (having a chronic disease, reports of a recent hospitalisation episode, deteriorated emotional status) was related to their reported burden. Preserving caregiver health is a noteworthy issue both for caregivers and, indirectly, for patient health.…”
Section: Discussionsupporting
confidence: 66%
“…(1) The variety of clinical statuses: for the first time, the health status of the persons with polyhandicap, aged 3-70 years, was described in terms of etiologies, comorbidities, associated handicaps, behavioral disorders, treatments and devices, severity and stability 9,18 ; (2) The evolving nature of the health status across the lifespan: for the first time, we showed the complex and specific needs of persons with polyhandicap in terms of care at every period of life, in particular the transition process from childhood to adulthood 10 ; (3) The adequacy of the care management: we showed that the adequacy of care management (in terms of care structures, nature of care provided) from objective indicators (such as the health severity and the age) seems less satisfactory than the perceived adequacy of the physicians 8 ; (4) The considerable impact on the quality of life for parents 19 and for health care workers caring for individuals with severe polyhandicap 16 . Readers may refer to the respective references for more details.…”
Section: Resultsmentioning
confidence: 95%
“…www.nature.com/scientificreports/ Third, the assessment of familial caregivers' experience is currently recognized as essential. There is a vast body of literature assessing caregiving in various chronic/severe diseases (such as cancer 23,24 , mental health diseases 25 , various neurologic diseases 26,27 , and cerebral palsy [28][29][30] ), but very few studies have assessed the impact of polyhandicap on caregivers 17,19 . Consideration of the experiences and concerns of families would strongly assist clinicians and health decision-making authorities in offering appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation